Clinical characteristics and outcomes of persistent bacteremia in patients with head and neck cancer in a tertiary care hospital - Kitaya, Shiori; Kanamori, Hajime; Ishii, Ryo; Katsumi, Makoto; Ikeda, Ryoukichi; Higashi, Kenjiro; Kakuta, Risako; Ohkoshi, Akira; Katori, Yukio (Frontiers in Medicine, 2024)
Introduction: Compared to other cancers, research on bloodstream infection in head and neck cancer is scarce, lacking comparative studies on persistent versus transient bacteremia outcomes. Methods: This retrospective survey examined patients with head and neck cancer undergoing blood culture at our center from June 2009 to May 2023. Blood culture-positive cases suspected of infection were divided into persistent bacteremia and transient bacteremia groups. We investigated their clinical, epidemiological, and microbiological features, including risk factors for persistent bacteremia and mortality. The primary outcome was 90-day mortality. Results: In this 97-patient cohort, 14 (14%) cases were assigned to the persistent bacteremia group. Catheter-related bloodstream infections were the leading cause of infection in both groups, consistently contributing to a high proportion of overall bloodstream infections. The mortality rate was generally higher in the persistent bacteremia group than in the transient bacteremia group (odds ratio [OR], 2.6; 95% confidence interval [CI], 0.6–11.1), particularly in the non-clearance subgroup (OR, 9; 95% CI, 0.5–155.2). Pyogenic spondylitis was a key risk factor for persistent bacteremia, while hypoalbuminemia increased mortality. Conclusion: In patients with bacteremia and head and neck cancer, persistent bacteremia was associated with higher mortality than was transient bacteremia. Bacteremia clearance in persistent bacteremia is thus crucial for prognostic improvement.